Fibrous free silicon-containing brake disc and preparation method thereof

By adding nylon fibers to the carbon fiber unidirectional cloth to form through holes, the problem of uneven density after the brake disc CVI treatment is solved, and the sample density uniformity after silicon permeation is achieved and the effect of liquid silicon is fully permeated, which improves the stability of the material and the stability of the manufacturing process.

CN119778398AActive Publication Date: 2025-04-08深圳市佰斯倍新材料科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411640534.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-08
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

After the CVI treatment, the internal and external density difference of the brake disc is too large, resulting in uneven density of the silicon seepage sample and the liquid silicon cannot penetrate the blank completely.

Method used

Add nylon fibers to the carbon fiber unidirectional cloth to form through holes, increasing the ability of deposited gas to diffuse into the fiber needle body, and thus uniformly increasing the inner and outer density of the CVI fiber blank.

Benefits of technology

By uniformly increasing the density of the CVI fiber blank, ensuring the density uniformity of the sample after silicon permeation, liquid silicon can completely penetrate the blank, improving the stability of the material and the stability of the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138310710000101
    Figure BDA0005138310710000101
Patent Text Reader

Abstract

The invention provides a fibrous free silicon-containing brake disc. The fibrous free silicon-containing brake disc comprises a plurality of carbon fiber unidirectional cloth layers and a plurality of carbon fiber web tire layers. The carbon fiber unidirectional cloth layers and the carbon fiber web tire layers are alternately arranged, the carbon fiber unidirectional cloth layers comprise carbon, silicon carbide and free silicon, part of free silicon in the free silicon is arranged in a fibrous shape to obtain fibrous free silicon, the length of the fibrous free silicon is 8-13 mm, the cross section area is 0.0018-0.2 mm < 2 >, and the carbon fiber unidirectional cloth layers and the carbon fiber web tire layers are alternately arranged. And the length direction of the fibrous free silicon is parallel to the carbon fiber direction of the carbon fiber unidirectional cloth. Appropriate nylon threads are added into long carbon fibers, the capability of diffusion of deposition gas to the interior of a needled carbon fiber blank during vapor deposition is improved by utilizing the characteristic that the nylon threads can form through holes, the internal and external density difference of the CVI fiber blank obtained after deposition is obviously reduced, and the stability of a material preparation process is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake disc manufacturing, and in particular to a brake disc containing fibrous free silicon and a preparation method thereof. Background Art

[0002] The brake disc is an important component installed on vehicles such as cars and motorcycles, used to brake the vehicle. It is usually located between the wheels and works with the brake calipers, brake pads, etc. in the brake system. The brake disc mainly plays the role of deceleration or emergency stop during the operation of the car. It is related to human life safety in emergencies, so it is particularly important. The speed of modern vehicles is getting higher and higher, and the requirements for brake discs as safety devices are also getting higher and higher. Carbon fiber reinforced carbon brake discs have become the only choice for high-speed vehicles. For example, airplanes, high-speed trains, sports cars, heavy-duty transport vehicles and high-end cars all use carbon fiber reinforced carbon brake discs. At present, brake discs are prepared by unidirectional cloth and mesh tire laminated needle punching. When the blank prepared by laminated needle punching passes through CVI, due to the small gap between the fibers, the deposited gas is not easy to diffuse into the inside, and it is easy to have the problem of high external deposition density and low internal deposition density. In the subsequent siliconization, the density of the siliconized sample will be uneven, and even the liquid silicon will not be able to completely penetrate the blank.

[0003] In order to solve the problem of density difference between the inside and outside of the material after deposition, a brake disc containing fibrous free silicon is proposed. Nylon fibers are added to the carbon fiber unidirectional cloth, and through holes are formed by using the nylon fibers, which greatly increases the ability of the deposited gas to diffuse into the interior of the fiber needle-punctured body. Summary of the invention

[0004] The present invention aims to provide a brake disc containing fibrous free silicon to solve the problem of large density difference between the inner and outer surfaces of the brake disc after CVI treatment.

[0005] To achieve this purpose, the present invention provides a brake disc containing fibrous free silicon, the brake disc containing fibrous free silicon comprises a plurality of carbon fiber unidirectional cloth layers and a plurality of carbon fiber mesh layers, the carbon fiber unidirectional cloth layers and the carbon fiber mesh layers are arranged alternately. The carbon fiber unidirectional cloth layers contain carbon, silicon carbide and free silicon, part of the free silicon in the free silicon is arranged in a fibrous shape to obtain fibrous free silicon, the length of the fibrous free silicon is 8-13 mm, and the cross-sectional area is 0.0018-0.2 mm 2 The length direction of the fibrous free silicon is parallel to the carbon fiber direction of the carbon fiber unidirectional cloth.

[0006] Preferably, the fiber bundle k value of the carbon fiber unidirectional cloth is 3-12k, a plurality of fiber bundles form a fiber bundle unit, the fibrous free silicon is located between adjacent fiber bundle units, and the fiber bundle unit contains 1-20 fiber bundles.

[0007] Preferably, the carbon content of the carbon fiber unidirectional cloth is 45-65vol%, the silicon carbide content is 30-50vol%, and the free silicon content is 5-15vol%; the carbon content of the carbon fiber mesh layer is 30-50vol%, the silicon carbide content is 40-60vol%, and the free silicon content is 5-12vol%.

[0008] Preferably, the fibrous free silicon accounts for 40-80% of the free silicon content.

[0009] Preferably, there are large-sized silicon carbide particles near the area where the fibrous free silicon is located, and the size of the silicon carbide particles is 15-50 microns.

[0010] The present invention also provides a method for preparing a brake disc containing fibrous free silicon, which is used to prepare the above-mentioned brake disc containing fibrous free silicon. The preparation method is as follows:

[0011] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, arranging a nylon thread every 1-20 fiber bundles, and the diameter of the nylon thread is 50-300 microns;

[0012] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0013] S3: placing the needle-punched carbon fiber blank into a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank, the deposition time is 150-300 hours, the deposition temperature is 950-1100° C., the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 80-200 L / h, and the nitrogen flow rate is 5-30 L / h;

[0014] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing to obtain a silicided blank;

[0015] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0016] Preferably, the density of the CVI fiber blank in step S3 is 1.25-1.45 g / cm 3 .

[0017] Preferably, in step S4, pure silicon powder having a mass 1.1 times that of the CVI fiber blank is pre-placed in the boron nitride crucible.

[0018] Preferably, the temperature of the siliconizing treatment in step S4 is 1600-1700° C., the holding time is 2-4 hours, and the furnace pressure is less than 1000 Pa.

[0019] Beneficial effects: The brake disc containing fibrous free silicon provided by the present invention has fibrous free silicon on the surface and inside of the brake disc, indicating that the density uniformity inside and outside the brake disc is improved during CVI deposition. After siliconization, the sample has good filling property of liquid silicon to the sample, and there is no unreacted area that has not been infiltrated by silicon. It can be seen that the brake disc has good stability. The present invention also proposes a method for preparing the brake disc containing fibrous free silicon, by adding appropriate nylon wire to the long carbon fiber, and utilizing the property of nylon wire that can form through holes to increase the ability of the deposited gas to diffuse into the interior of the needle-punched carbon fiber blank during vapor deposition. The difference in density between the inside and outside of the CVI fiber blank obtained after deposition is significantly reduced, which not only improves the stability of the material preparation process. The process also greatly reduces the deposition time of CVI, allowing the deposited blank to reach a higher density in a shorter time, shortening the manufacturing cycle of the material. At the same time, the CVI fiber blank with uniform density is conducive to the filling effect of liquid silicon on the blank in the subsequent siliconization treatment. The liquid silicon penetrates well into the interior of the CVI fiber blank. At the same time, the density of the blank is uniform after vapor deposition, which can better protect the carbon fiber during siliconization, preventing the carbon fiber from being corroded and reducing the strength of the brake disc. DETAILED DESCRIPTION

[0020] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention provides a brake disc containing fibrous free silicon, the brake disc containing fibrous free silicon comprises a plurality of carbon fiber unidirectional cloth layers and a plurality of carbon fiber mesh layers, the carbon fiber unidirectional cloth layers and the carbon fiber mesh layers are arranged alternately. The carbon fiber unidirectional cloth layers contain carbon, silicon carbide and free silicon, part of the free silicon in the free silicon is arranged in a fibrous shape to obtain fibrous free silicon, the length of the fibrous free silicon is 8-13 mm, and the cross-sectional area is 0.0018-0.2 mm 2 The length direction of the fibrous free silicon is parallel to the carbon fiber direction of the carbon fiber unidirectional cloth.

[0022] The fiber bundle k value of the carbon fiber unidirectional cloth is 3-12k, a plurality of fiber bundles form a fiber bundle unit, the fibrous free silicon is located between adjacent fiber bundle units, and the fiber bundle unit contains 1-20 fiber bundles, that is, 3-12 fiber filaments form a fiber bundle, and then 1-20 fiber bundles together form the fiber bundle unit.

[0023] The carbon fiber unidirectional cloth has a carbon content of 45-65 vol%, a silicon carbide content of 30-50 vol%, and a free silicon content of 5-15 vol%; the carbon fiber web layer has a carbon content of 30-50 vol%, a silicon carbide content of 40-60 vol%, and a free silicon content of 5-12 vol%.

[0024] The fibrous free silicon accounts for 40-80% of the free silicon content.

[0025] There are large-size silicon carbide particles near the area where the fibrous free silicon is located, and the size of the silicon carbide particles is 15-50 microns.

[0026] The present invention also provides a method for preparing a brake disc containing fibrous free silicon, which is used to prepare the above-mentioned brake disc containing fibrous free silicon. The preparation method is as follows:

[0027] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, arranging a nylon thread every 1-20 fiber bundles, and the diameter of the nylon thread is 50-300 microns;

[0028] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0029] S3: placing the needle-punched carbon fiber blank into a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank, the deposition time is 150-300h, the deposition temperature is 950-1100°C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 80-200L / h, and the nitrogen flow rate is 5-30L / h; no deposition gas is passed during the heating stage of chemical vapor deposition, and the deposition gas is introduced 5-10 minutes before the predetermined temperature is reached, and the nylon line is decomposed during the heating process (without the deposition gas), and the through holes formed are prepared for subsequent deposition processing;

[0030] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing to obtain a silicided blank;

[0031] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0032] The density of the CVI fiber blank in step S3 is 1.25-1.45 g / cm 3 .

[0033] In step S4, pure silicon powder having a mass 1.1 times that of the CVI fiber blank is pre-placed in the boron nitride crucible.

[0034] The temperature of the siliconizing treatment in step S4 is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa.

[0035] Example 1

[0036] This embodiment provides a brake disc containing fibrous free silicon, and the preparation steps are as follows:

[0037] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, setting a nylon line every 10 fiber bundles, and the diameter of the nylon line is 150 microns;

[0038] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0039] S3: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 200 h, the deposition temperature is 1000 ° C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.35 g / cm 3 ;

[0040] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0041] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0042] Example 2

[0043] This embodiment provides a brake disc containing fibrous free silicon, and the preparation steps are as follows:

[0044] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, setting a nylon line every 10 fiber bundles, and the diameter of the nylon line is 300 microns;

[0045] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0046] S3: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 180 hours, the deposition temperature is 1000°C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.35 g / cm 3 ;

[0047] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0048] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0049] Example 3

[0050] This embodiment provides a brake disc containing fibrous free silicon, and the preparation steps are as follows:

[0051] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, setting a nylon line every 5 fiber bundles, and the diameter of the nylon line is 150 microns;

[0052] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0053] S3: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 200 h, the deposition temperature is 1000 ° C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.39 g / cm 3 ;

[0054] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0055] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0056] Example 4

[0057] This embodiment provides a brake disc containing fibrous free silicon, and the preparation steps are as follows:

[0058] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, setting a nylon line every 10 fiber bundles, and the diameter of the nylon line is 150 microns;

[0059] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0060] S3: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 150 h, the deposition temperature is 1000 ° C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.29 g / cm 3 ;

[0061] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0062] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0063] Comparative Example 1

[0064] This comparative example provides a brake disc, and the preparation steps are as follows:

[0065] S1: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the overlapping is performed to obtain a needle punched carbon fiber blank;

[0066] S2: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 200 h, the deposition temperature is 1000 ° C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.20 g / cm 3 ;

[0067] S3: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0068] S4: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0069] Comparative Example 2

[0070] This comparative example provides a brake disc containing fibrous free silicon, and the preparation steps are as follows:

[0071] S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, setting a nylon line every 10 fiber bundles, and the diameter of the nylon line is 400 microns;

[0072] S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank;

[0073] S3: The needle-punched carbon fiber blank is placed in a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank. The deposition time is 200 h, the deposition temperature is 1000 ° C, the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 150 L / h, the nitrogen flow rate is 20 L / h, and the density of the CVI fiber blank is 1.36 g / cm 3 ;

[0074] S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, pre-placing pure silicon powder 1.1 times the mass of the CVI fiber blank in the boron nitride crucible, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing treatment to obtain a silicided blank, wherein the siliconizing treatment temperature is 1650° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa;

[0075] S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

[0076] The brake discs prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 were tested. The test method is:

[0077] The density is tested using GB / T 25995-2010 “Test method for density and apparent porosity of fine ceramics”.

[0078] The bending strength is tested using the GBT_65669-2006 fine ceramic bending strength test method.

[0079] The test data is shown in Table 1.

[0080] Table 1 Brake disc test data of Examples 1-4 and Comparative Examples 1-2

[0081]

[0082] From the above test data, it can be seen that in Example 1, nylon wire is set in the fiber, which increases the ability of the deposition gas to diffuse inside the blank. After siliconization, the density of the inner and outer circles of the sample is not much different, and the strength is relatively high. In Example 2, the nylon wire is replaced with 300 microns, and the time required to achieve the same deposition density is reduced. The density of the sample after siliconization does not change much, and the strength is also maintained at a high level. In Example 3, the fiber bundles between the nylon fibers are reduced to 5. At the same CVI time, the sample density (i.e., the CVI fiber blank) increases from 1.35 g / cm 3 Increased to 1.39g / cm 3 As the density of the CVI blank increases, the corrosion of silicon on the carbon fiber decreases during siliconization, the carbon content in the sample increases, and the strength of the material is improved; in Example 4, the CVI deposition time is reduced to 150h, and the density of the sample after deposition is 1.29g / cm 3 The porosity of the sample is improved. During siliconization, silicon reacts more with deposited carbon and part of the carbon fibers, but its strength still reaches 98MPa, indicating that this method can be used to prepare a carbon-ceramic brake disc that meets the performance requirements in a shorter CVI time; Comparative Example 1 does not set nylon wire, and the density of the sample after CVI is low (it is difficult for the deposited gas to diffuse into the interior of the blank). After siliconization, the density difference between the inner and outer rings of the sample is large, and due to the insufficient deposited carbon content, silicon corrodes the fiber greatly, and the strength of the sample is greatly reduced; Comparative Example 2 uses 400μm nylon wire. After 200h deposition, the density of the sample is similar to that of the actual sample. Example 1 is not much different, but the density of the sample after siliconization is insufficient. This is because the holes formed at 400μm are too large, and the capillary force on liquid silicon is insufficient. There are some holes in the core of the sample that are not filled with silicon, resulting in low sample density and low strength. Unlike other schemes, the density of the outer circle of the sample after siliconization in this scheme is greater than that of the inner circle. This is because the surfaces of silicon and CVI samples have good wettability, and silicon is easy to infiltrate the surface area, and does not require long-distance penetration through capillary force. Therefore, the density of the area where the outer circle and silicon are easily in contact is higher, but there are still fibrous holes that are not filled with silicon.

[0083] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.

Claims

1. A brake disc containing fibrous free silicon, comprising a plurality of layers of carbon fiber unidirectional cloth layers and a plurality of layers of carbon fiber web layers, characterized in that: The carbon fiber unidirectional cloth layer and the carbon fiber web layer are arranged alternately, the carbon fiber unidirectional cloth layer contains carbon, silicon carbide and free silicon, part of the free silicon is arranged in a fibrous shape to obtain fibrous free silicon, the fibrous free silicon has a length of 8-13 mm and a cross-sectional area of ​​0.0018-0.2 mm 2 The length direction of the fibrous free silicon is parallel to the carbon fiber direction of the carbon fiber unidirectional cloth.

2. The brake disc containing fibrous free silicon according to claim 1, characterized in that: The fiber bundle k value of the carbon fiber unidirectional cloth is 3-12k, a plurality of fiber bundles form a fiber bundle unit, the fibrous free silicon is located between adjacent fiber bundle units, and the fiber bundle unit contains 1-20 fiber bundles.

3. The brake disc containing fibrous free silicon according to claim 1, characterized in that: The carbon fiber unidirectional cloth has a carbon content of 45-65 vol%, a silicon carbide content of 30-50 vol%, and a free silicon content of 5-15 vol%; the carbon fiber web layer has a carbon content of 30-50 vol%, a silicon carbide content of 40-60 vol%, and a free silicon content of 5-12 vol%.

4. The brake disc containing fibrous free silicon according to claim 1, characterized in that: The fibrous free silicon accounts for 40-80% of the free silicon content.

5. The brake disc containing fibrous free silicon according to claim 4, characterized in that: There are large-size silicon carbide particles near the area where the fibrous free silicon is located, and the size of the silicon carbide particles is 15-50 microns.

6. A method for preparing a brake disc containing fibrous free silicon, for preparing a brake disc containing fibrous free silicon as claimed in any one of claims 1 to 5, characterized in that: The preparation method is as follows: S1: Weaving continuous carbon fiber bundles and nylon fibers into carbon fiber unidirectional cloth according to a predetermined arrangement interval, arranging a nylon thread every 1-20 fiber bundles, and the diameter of the nylon thread is 50-300 microns; S2: overlapping the carbon fiber unidirectional cloth and the carbon fiber web, and performing a needle punching treatment each time the carbon fiber unidirectional cloth and the carbon fiber web are overlapped to obtain a needle punched carbon fiber blank; S3: placing the needle-punched carbon fiber blank into a chemical vapor infiltration furnace for chemical vapor deposition to obtain a CVI fiber blank, the deposition time is 150-300 hours, the deposition temperature is 950-1100° C., the gas used for deposition is methane, the dilution gas is nitrogen, the methane flow rate is 80-200 L / h, and the nitrogen flow rate is 5-30 L / h; S4: grinding the surface of the CVI fiber blank, placing the CVI fiber blank in a boron nitride crucible after grinding, and then placing the boron nitride crucible in a high-temperature vacuum furnace for siliconizing to obtain a silicided blank; S5: grinding the surface of the siliconized body and processing the outer contour dimensions to obtain the brake disc containing fibrous free silicon.

7. The method for preparing a brake disc containing fibrous free silicon according to claim 6, characterized in that: The density of the CVI fiber blank in step S3 is 1.25-1.45 g / cm 3 .

8. The method for preparing a brake disc containing fibrous free silicon according to claim 6, characterized in that: In step S4, pure silicon powder having a mass 1.1 times that of the CVI fiber blank is pre-placed in the boron nitride crucible.

9. The method for preparing a brake disc containing fibrous free silicon according to claim 6, characterized in that: The temperature of the siliconizing treatment in step S4 is 1600-1700°C, the holding time is 2-4h, and the furnace pressure is less than 1000Pa.

Citation Information

Patent Citations

  • Method for preparing SiCf / SiC compound material by combination of chemical vapor carbon deposition process and gas phase siliconizing process

    CN101555139A

  • Method for preparing carbon-silicon carbon composite material and product thereof

    CN102924106A

  • Preparation method of fiber-enhanced silicon carbide composite material

    CN104478460A

  • Preparation method of ceramic reinforced carbon / carbon composite material brake disc

    CN109372916A

  • Carbon / carbon heater with silicon carbide coating for Czochralski silicon single crystal furnace

    CN111072399A